Bi-level model for integrated energy service providers in joint electricity and carbon P2P market. (20th March 2023) - Sun, Guoqiang; Zhang, Zheyu; Zhou, Yizhou; Han, Haiteng; Zang, Haixiang; Wei, Zhinong
Abstract: The integration of local power generation units into integrated energy service providers (IESPs) can enable IESPs to realize optimal resource allocation and provide multiple energy services. We propose a bi-level model for IESPs participating in joint electricity and carbon peer-to-peer (P2P) markets. To reduce carbon emissions, we set up carbon capture equipment in IESPs to collect carbon dioxide for the synthesis of methane and methanol. Furthermore, we propose a P2P transaction mechanism based on carbon emission flow and build a bi-level model to achieve the collaborative optimization of IESPs and distribution system operators. Additionally, we utilize the alternating direction method of multipliers (ADMM) algorithm to protect the privacy of users in the P2P transaction process. Simulation results of a distribution network with multiple IESPs demonstrate that the proposed model reduces the overall carbon emissions, allocates part of the carbon emission responsibilities to loads, and reduces the carbon emission costs of P2P transaction participants.